2022
DOI: 10.4062/biomolther.2022.066
|View full text |Cite
|
Sign up to set email alerts
|

PRR16/Largen Induces Epithelial-Mesenchymal Transition through the Interaction with ABI2 Leading to the Activation of ABL1 Kinase

Abstract: Advanced or metastatic breast cancer affects multiple organs and is a leading cause of cancer-related death. Cancer metastasis is associated with epithelial-mesenchymal metastasis (EMT). However, the specific signals that induce and regulate EMT in carcinoma cells remain unclear. PRR16/Largen is a cell size regulator that is independent of mTOR and Hippo signalling pathways. However, little is known about the role PRR16 plays in the EMT process. We found that the expression of PRR16 was increased in mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that c‐Abl has three NLS domains and one NES domain, which leads to c‐Abl shuttle between nuclei and cytoplasm, therefore displaying different functions 34 . Nuclear c‐Abl displays pro‐apoptotic activity upon DNA damage, 35 while cytoplasmic c‐Abl is oncogenic by activating a series of oncoprotein substrates including STAT3 signalling 7,24,36 . Although it is known that the chaperone protein 14‐3‐3α/β binds to c‐Abl and arrests it in cytosol, but the detailed mechanism is not well known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that c‐Abl has three NLS domains and one NES domain, which leads to c‐Abl shuttle between nuclei and cytoplasm, therefore displaying different functions 34 . Nuclear c‐Abl displays pro‐apoptotic activity upon DNA damage, 35 while cytoplasmic c‐Abl is oncogenic by activating a series of oncoprotein substrates including STAT3 signalling 7,24,36 . Although it is known that the chaperone protein 14‐3‐3α/β binds to c‐Abl and arrests it in cytosol, but the detailed mechanism is not well known.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Nuclear c‐Abl displays pro‐apoptotic activity upon DNA damage, 35 while cytoplasmic c‐Abl is oncogenic by activating a series of oncoprotein substrates including STAT3 signalling. 7 , 24 , 36 Although it is known that the chaperone protein 14‐3‐3α/β binds to c‐Abl and arrests it in cytosol, but the detailed mechanism is not well known. In the present study, we found the underlying mechanism is probably also associated with the stabilization and the binding of 14‐3‐3α/β to c‐Abl induced by USP7.…”
Section: Discussionmentioning
confidence: 99%
“…The co-immunoprecipitation (co-IP) assays were performed as previously described ( Kang et al ., 2022 ). Briefly, cells were trypsinized, centrifuged, and the pellets were washed with cold phosphate-buffered saline and resuspended in lysis buffer [50 mM Tris-HCl pH 7.2, 150 mM NaCl, 1% Triton X-100, and a protease inhibitor cocktail containing 1 µg/mL leupeptin, 1 µg/mL pepstatin, 2 µg/mL aprotinin, and 200 µg/mL phenylmethylsulfonyl fluoride (PMSF)].…”
Section: Methodsmentioning
confidence: 99%
“…Cell migration was assessed using Transwell chambers (8-mm pore size; Corning Costar, Cambridge, MA, USA) as described previously ( Kang et al ., 2022 ).…”
Section: Matrerials and Methodsmentioning
confidence: 99%